THE VITALITY OF THE NIAS LANGUAGE IN THE ERA OF GLOBALIZATION: A SOCIOLINGUISTIC STUDY OF THE YOUNGER GENERATION - Opirman Waruwu (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the vitality of the Nias language (Li Niha) among young speakers in the era of globalization using UNESCO’s (2003) Language Vitality and Endangerment framework. A convergent mixed methods design was employed involving 150 participants aged 15–30 years from Gunungsitoli, Telukdalam, and Mandrehe. Data were collected through questionnaires, in-depth interviews, and non-participant observations and analyzed using descriptive statistics, binary logistic regression, and reflexive thematic analysis. The findings reveal that Li Niha has a composite vitality score of 2.71 out of 5, placing it in the vulnerable category. Language use remains high in traditional ceremonies (90.7%) and communication with elderly family members (83.3%), but declines substantially in formal education (9.0%) and digital communication (9.0%). Intergenerational transmission shows a sharp decrease from 76.0% among grandparents and parents to 21.3% among youth and younger siblings. Logistic regression identified urban residence (OR = 3.20), social media use (OR = 2.33), and higher education (OR = 2.06) as significant predictors of language shift, while parental use of Li Niha at home (OR = 0.26) emerged as the strongest protective factor. The study highlights the urgency of family-based and digitally integrated language revitalization strategies to ensure the future sustainability of Li Niha.